2021
DOI: 10.1186/s43054-021-00071-1
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of emerging multidrug-resistant organisms and its impact on the outcome in the pediatric intensive care

Abstract: Background Healthcare-associated infections (HCAI) are a worldwide threat in intensive care units particularly in the pediatric intensive care units with a major cause of morbidity and mortality among this age group. The aim of the study is to determine the prevalence and risk factors predisposing to multidrug-resistant organisms (MDROs) infections among pediatric intensive care unit (PICU) patients at Ain Shams Pediatric University Hospitals as well as determining mortality and morbidity rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
4
6
1
Order By: Relevance
“…A similar trend was also reported locally in Egypt by Khalifa et al [ 29 ], as well as globally among patients with underlying malignancies in tertiary hospitals by Paul et al [ 30 ] and Garg et al [ 6 ]. This was in contrast to the study carried out by Rezk et al in a critical care unit in Egypt that reported Acinetobacter baumannii as the predominant organism [ 31 ]. Moreover, Sheth et al found that among ICU patients, Acinetobacter spp.…”
Section: Discussioncontrasting
confidence: 93%
“…A similar trend was also reported locally in Egypt by Khalifa et al [ 29 ], as well as globally among patients with underlying malignancies in tertiary hospitals by Paul et al [ 30 ] and Garg et al [ 6 ]. This was in contrast to the study carried out by Rezk et al in a critical care unit in Egypt that reported Acinetobacter baumannii as the predominant organism [ 31 ]. Moreover, Sheth et al found that among ICU patients, Acinetobacter spp.…”
Section: Discussioncontrasting
confidence: 93%
“…Rezk et al found a significant relationship between MDR organisms and underlying pulmonary disease. 24 In our study, cardiac disease was found as an additional risk factor along with respiratory disease for MDR infection. Age below 2 years along with more than 3 days of hospital stay was identified as a risk factor for the acquisition of MDR.…”
Section: Discussionsupporting
confidence: 47%
“…In a study by Rezk et al, authors evaluated 282 pediatric ICU patients of which only 9.2% were colonized with MDR Gram-negative bacteria; of them, nearly half were affected by Acinetobacter species (50%). 24 In another study by Rhim et al, in subarachnoid hemorrhage (SAH) patients, extended-spectrum β-lactamase producing bacteria were the commonest ( E. coli and K. pneumoniae ) followed by methicillin-resistant Staphylococcus aureus , MDR Gram-negative rods, and vancomycin-resistant enterococci. 25 In our study, out of 274 patients enrolled, 31 MDR episodes were identified.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study in Egypt, only 9.2% of the cases tested positive for MDRO [15] . This study found that one-third of cultures tested positive for MDRO, indicating a lack of antimicrobial stewardship programs and inadequate implementation of infection control policies [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%